2007
DOI: 10.1007/s10725-006-9157-8
|View full text |Cite
|
Sign up to set email alerts
|

Leaf senescence and grain filling affected by post-anthesis high temperatures in two different wheat cultivars

Abstract: High temperature is a major factor affecting grain yield and plant senescence in wheat growing regions of central and east China. In this study, two different wheat cultivars, Yangmai 9 with low-grain protein concentration and Xuzhou 26 with high-grain protein concentration, were exposed to different temperature regimes in growth chambers during grain filling. Four day/night temperature regimes of 34°C/ 22°C, 32°C/24°C, 26°C/14°C, and 24°C/16°C were established to obtain two daily temperatures of 28 and 20°C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 20 publications
8
107
0
Order By: Relevance
“…During normal plant growth when the photon intensity is within the range of the utilizing capacity of chloroplasts for CO 2 -fixation, the generation rate of AOS is very low, and these molecules are effectively scavenged. Several researchers observed that during the time of fast growth as well as the plant with greater biomass producing capacity showed greater activities of antioxidant enzyme activities to prevent the excess production of AOS (Gara et al 2000;Hideg et al 2002;Zhao et al 2007). The association of different antioxidant enzymes with Pn and other photosynthetic parameters were showed highly significant positive correlation (Table 1).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…During normal plant growth when the photon intensity is within the range of the utilizing capacity of chloroplasts for CO 2 -fixation, the generation rate of AOS is very low, and these molecules are effectively scavenged. Several researchers observed that during the time of fast growth as well as the plant with greater biomass producing capacity showed greater activities of antioxidant enzyme activities to prevent the excess production of AOS (Gara et al 2000;Hideg et al 2002;Zhao et al 2007). The association of different antioxidant enzymes with Pn and other photosynthetic parameters were showed highly significant positive correlation (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…The association of different antioxidant enzymes with Pn and other photosynthetic parameters were showed highly significant positive correlation (Table 1). The significant association was due to the overall decrease of leaf function during natural senescence of flag leaves (Yamazaki and Kamimura 2001;Zhao et al 2007;Falqueto et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperatures may damage plant cell membranes resulting in photosynthesis reductions. Heat stress induces the production of reactive oxygen species, which can bring about peroxidation of membrane lipids, leading to membrane injury (Blum and Ebercon, 1981;Almeselmani et al, 2006;Leshem, 1992), photosynthesis impairment and leaf senescence (Zhao et al, 2007). As observed for other stressful conditions, the ability to maintain membrane integrity and, hence, cell compartmentalization and metabolism, is crucial for plants survival under heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…High temperature during grain filling stage is an important yield limiting factor in wheat (Zhao et al 2007). It has been reported that single grain mass falls by 3-5% for every 1°C rise in temperature above 18°C (McDonald et al 1983).…”
Section: Introductionmentioning
confidence: 99%